2022
DOI: 10.1108/jaar-04-2021-0086
|View full text |Cite
|
Sign up to set email alerts
|

The non-financial reporting practices of Hungarian listed public interest entities considering the 2014/95/EU Directive

Abstract: PurposeThis paper aims to investigate the non-financial reporting (NFR) practices of Hungarian listed public interest entities for 2016–2018 in terms of the required disclosure content based on the 2014/95/EU Directive (ED).Design/methodology/approach The authors apply content analysis methodology on Hungarian firms subject to mandatory reporting under the ED. The target variable in the multivariate model is the reporting quality (Qi) measured by a combined index.Findings The authors find that the ED had a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 63 publications
2
24
0
2
Order By: Relevance
“…The aim of our investigation was to determine whether ED improved the reporting of nonfinancial and diversity information. Our study revealed a statistically significant improvement in reporting, which confirms not only our hypothesis H1, but also the first empirical findings regarding the effect of ED on particular member states, sectors or specific disclosure requirements and the trend toward improvement in disclosure identified therein (Caputo et al, 2019;Mion and Loza Adaui, 2019;Agostini et al, 2021;Korca et al, 2021;Matuszak and R ozanska, 2021;Posadas and Tarquinio, 2021;Carmo and Ribeiro, 2022;Lippai-Makra et al, 2022). However, in line with our hypothesis H2, the improvement is not evident in all information categories.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The aim of our investigation was to determine whether ED improved the reporting of nonfinancial and diversity information. Our study revealed a statistically significant improvement in reporting, which confirms not only our hypothesis H1, but also the first empirical findings regarding the effect of ED on particular member states, sectors or specific disclosure requirements and the trend toward improvement in disclosure identified therein (Caputo et al, 2019;Mion and Loza Adaui, 2019;Agostini et al, 2021;Korca et al, 2021;Matuszak and R ozanska, 2021;Posadas and Tarquinio, 2021;Carmo and Ribeiro, 2022;Lippai-Makra et al, 2022). However, in line with our hypothesis H2, the improvement is not evident in all information categories.…”
Section: Discussionsupporting
confidence: 89%
“…Lippai-Makra et al (2022) investigated the impact of the directive on Hungarian companies and found a moderate improvement in quality. In the same year, Carmo and Ribeiro (2022) also reported a positive impact on reporting due to the directive in their study of listed Portuguese companies.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors highlight the influence of the characteristics of the company (size and activity sector) and the particularities of each country's regulatory framework on the degree of response to regulation (Caputo et al, 2020;Ferrer et al, 2020;García-Benau et al, 2022;Sierra-Garcia et al, 2018). It has also been observed that the existence of previous legislation at the national level on disclosure of environmental information and the previous experience of the company in disclosure of information on sustainability affect compliance with Directive 2014/95/EU (Carmo & Ribeiro, 2022;García-Sánchez, Sierra-García, & García-Benau, 2022;Lippai-Makra et al, 2022;Mion & Loza Adaui, 2019;Posadas & Tarquinio, 2021). Future studies could address these aspects.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Lippai-Makra et al (2022) evaluated the effects of the Directive 2014/95/EU in Hungaria. Adopting a theoretical framework used in previous studies about non-financial reporting in Europe, the authors collected interesting insights about non-financial regulation in developing countries.…”
Section: The Non-financial Reporting Practices Of Hungarian Listed Pu...mentioning
confidence: 99%